2019
DOI: 10.1002/jum.14919
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Placental Microvasculature Using Superb Microvascular Imaging

Abstract: uses clutter suppression to extract flow signals at rapid frame rates, which provides high-resolution vessel-branching details without the need for contrast agents. The potential diagnostic benefits of SMI, as described in other areas of medicine, requires further exploration during pregnancy. In this pictorial essay, we demonstrate the complementary use of SMI compared to conventional Doppler ultrasound and how it may improve our ability to characterize placental microvascular patterns without the need for ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…reported a direct finding of shed decidual blood flows, and Hasegawa et al . reported an indirect finding of the unique properties of intraplacental chorionic blood vessels 10,11 . In addition, in our case, these findings were detected using a conventional transabdominal probe as opposed to high‐resolution 18‐MHz SMI.…”
Section: Discussionmentioning
confidence: 47%
“…reported a direct finding of shed decidual blood flows, and Hasegawa et al . reported an indirect finding of the unique properties of intraplacental chorionic blood vessels 10,11 . In addition, in our case, these findings were detected using a conventional transabdominal probe as opposed to high‐resolution 18‐MHz SMI.…”
Section: Discussionmentioning
confidence: 47%
“…Mack et al reported a direct finding of missing decidual blood flows, and Hasegawa et al reported indirect findings of unique characteristics of intraplacental chorionic vessels. 5,6 We also diagnosed PAS by finding missing decidual tissues directly, using SMI. Spontaneous uterine rupture is rare in an undamaged uterus.…”
Section: Discussionmentioning
confidence: 99%
“…MVFI provides new opportunities for noninvasive characterization of the placental microvascular pattern during pregnancy without contrast [33]. MVFI shows the intraplacental small vessels more clearly than CDI or PDI [33] while maintaining relatively high frame rates (Figure 14A-C) [56]. A recent longitudinal study has shown that it is feasible to use MVFI to assess the development of the placental microvascularization throughout normal pregnancies [57].…”
Section: Placentamentioning
confidence: 99%
“…In pregnancies affected by or at risk of fetal growth restriction or pre-eclampsia, MVFI provides new opportunities for noninvasive characterization of the placental microvascular pattern from the first to the third trimester [33,[56][57][58]. MVFI can also be used to confirm the absence of blood flow to, among others, a multicystic dysplastic kidney, an absent kidney [40], or placental lakes [50,51].…”
Section: Special Indications Of New Modes Of Cfimentioning
confidence: 99%